Olonets Zemstvo in the political life of the Russian Empire (1867-1913) - Badanov Vadim Georgiyevich (Studia Humanitatis)
The government assigned economic functions to the zemstvo institutions, but contrary to all expectations the zemstvos engaged in “politics” and by the beginning of the 20th century had become an active political force. In this context “the political aspect” of activity of Olonets zemstvo being a peculiar one because it didn’t become the conductor of liberal ideas as the majority of the Russian Empire zemstvos is under considerable interest. Throughout the entire period of its existence (1867-1918) it was the zemstvo of pragmatists and realists. The territorial movement here, unlike other territorial provinces, was loyal in relation to the government and took firm conservative and guarding positions up to March, 1917.